Research on visual search strategies during apparatus throw-and-catch in group rhythmic gymnastics - Zhou, C.; Cai, Y.; Li, K.; Zhang, X.; Tang, C. (Frontiers in Psychology, 2025)
Objective: This study aimed to investigate the visual search characteristics and strategies of expert rhythmic gymnasts during apparatus throw-and-catch tasks under different apparatus types and difficulty levels, in order to provide theoretical support for optimizing routine choreography and designing effective visual training programs.